AN EMPIRICAL STUDY ON VETO POWER OF THE PRESIDENT - A, AHANA JENCY. (International Journal of Psychosocial Rehabilitation, 2020)
Article 52 states approximately the strength of the president. Well who is a president andWhat is the position of a president? A president is the one who governs the fullCountry. He’s the only who has absolutely the and real power to make and government Decisions. The president has many powers wherein he can appearance after the states,The USA Legislature, the parliament which includes events. That is Lok Sabha and the Rajya Sabha. The Lok sabha is considered to be the human beings’shouseAs it includes 545 individuals and Rajya Sabha consists of 238 individuals. The President has a right away access to both houses of the parliament. The president Indeed has a totally huge task to cope with. In which he has to manipulate the usa’s Affairs where he has to look after the authorities of India’s governance. In Which he has a splendid responsibility to perform, administer the numerous sources led with the aid of the Parliament. And appearance after the bills or ordinances handed wherein he need to Have a detailed communication with the vice president, council of ministers, in which In he must have a should decision and make up and end his challenge and give hisBest to the fullest.Iage, education qualification ,: veto strength , 1555,Random Sampling Method